Тревожные расстройства в общей врачебной практике: аспекты клиники и терапии - В. А. Гуров; В. Э. Медведев (SINAPS LLC, 2011)
Early diagnosis and early initiation of adequate therapy in the spectrum of anxiety disorders (AD) is one of the pressing problems of modern medicine, which is determined by the high prevalence and significant impact on quality of life of AD is not only burdened with somatic patients, but also physically healthy people. The article deals with aspects of diagnosis and treatment of TS in the general medical network, in particular, describes the currently recommended regimen of the drug Phenorelaxan and benefits of this drug.